A Diplexer Bandpass Filter For Dual Band RF Front-End Receiver At 2.4 GHz And 5.75 GHz - Azman, Ahmad; Abdul Rani, Othman; Zahriladha, Zakaria; Kamil, Pongot (Engg Journals Publications, 2016)
A new approach for designing a diplexer for dual-band bandpass filter (BPF) using a parallel coupled microstrip line filter is presented in this paper. The proposed diplexer consists of two fundamental resonant modes and the resonant characteristics has been investigated usingAdvanced Design System (ADS) 2011 software. To validate the design and analysis, two band-pass BPF were fabricated and measured. It shown that the measured and simulated performance are in good agreement. A dual-band response BPF that operates at 2.4 GHz and 5.75 GHz is designed and implement for IEEE 802.11a/b/g applications.